Pemanfaatan Teknologi dalam Pembelajaran Tematik untuk Meningkatkan Hasil Belajar Peserta Didik di Kelas IV Sekolah Dasar - Rifky Maulana Akbar (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2022)
The method used in this study is a literature review. Literature review is the approach taken by the researchers in this study. One of the scientific methods used in a research that focuses on a particular topic. The literature review method used in this study has five stages or steps, but researchers only use four of them. Based on the findings from various experiments of each researcher, students who use learning video media have better science learning outcomes than students who do not use video media. . a number of supporting arguments that the use of video learning media in conjunction with learning activities will increase profitability because it will provide direct learning experiences to students and does not require a lot of teacher involvement.